1995
DOI: 10.1111/j.1365-2303.1995.tb00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Ki‐1‐positive anaplastic large cell lymphoma initially diagnosed as Hodgkin's disease by fine needle aspiration (FNA) cytology

Abstract: A 45-year-old male presented with a large mass in the left axilla. FNA cytology was interpreted as Hodgkin's disease (HD), lymphocyte depletion (LD) type, but histopathologic and immunohistochemical examination showed features of Ki-1-positive anaplastic large cell lymphoma. Unrepresentative sampling by the FNA from the tumour periphery resulted in a false impression of dual reactive and neoplastic cell populations, which together with the frequent Reed-Sternberg-like cells led to the initial erroneous impress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…One of the most difficult situations in diagnostic cytopathology is the differentiation between HL and ALCL, 19,23 mainly because of the overlapping morphologic features of the 2 diseases: both are characterized by abnormal cells in a background of reactive lymphocytes and granulocytes. The number of abnormal cells and their spectrum differ significantly in each disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most difficult situations in diagnostic cytopathology is the differentiation between HL and ALCL, 19,23 mainly because of the overlapping morphologic features of the 2 diseases: both are characterized by abnormal cells in a background of reactive lymphocytes and granulocytes. The number of abnormal cells and their spectrum differ significantly in each disease.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the English-language literature revealed very few studies discussing in detail the cytomorphologic features of the 2 entities. [21][22][23][24] To our knowledge, no study has attempted to comprehensively differentiate the cytomorphologic characteristics of either disease. In this study we attempted to determine if we could differentiate between the 2 entities by identifying the salient cytomorphologic features of each one.…”
Section: Diagnostic Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…14 Cytodiagnosis of Ki-1 ALCL by fine needle aspiration has been described in the form of isolated case reports or small series of cases during the past decade. 1,2,9,11,12,[15][16][17]19,[22][23][24] Still more rare is the diagnosis of this neoplasm by exfoliative cytology, such as urine, 21 cerebrospinal fluid, 6,19 ascitic fluid 5 and pleural effusion. 4-6,10,13,18, 19 We report a case that was diagnosed initially by cytologic examination of pleural fluid and confirmed by immunocytochemical staining.…”
Section: Background: Reports On Cytodiagnosis Of Ki-1-positive Anaplamentioning
confidence: 99%
“…Confusion with ALCL is a well-known pitfall not only in cytology [7][8][9][10] but also in histologic and immunohistochemical studies. 11 the tumor population and smoother nuclear contours should suggest nasopharyngeal carcinoma rather than HD.…”
mentioning
confidence: 99%